Prayer and koinonia in the Fourth Gospel - Barus, Armand (HTS teologiese studies, 2023)
Prayer, the central spirituality in the theological and ethical life of Christ’s disciples, has not yet received significant attention from Johannine scholars. Although some scholars emphasised and discussed prayer in the New Testament, Johannine scholars have failed to recognise the significance of prayer in the Fourth Gospel. Using narrative criticism the article aims to uncover the relationship between prayer and koinonia in the Fourth Gospel. The research on the theme of prayer and koinonia conducted in the Fourth Gospel has yielded the finding that prayer was a manifestation of abiding in Jesus. Koinonia was a form of prayer.Contribution: The article fills the lacuna in Johannine studies, more specifically, in the field of prayer and koinonia. The article, which is in line with the scope of HTS Theological Studies, and offers a new interpretation of prayer and koinonia in the Fourth Gospel.